Gluteal Muscle Activation During Common Yoga Poses - B.J. Lehecka; Sydney Stoffregen; Adam May; Jacob Thomas; Austin Mettling; Josh Hoover; Rex Hafenstine; Nils A Hakansson (International Journal of Sports Physical Therapy)
# Background